The Development Strategy of Pondokdadap Coastal Fishing Port, Malang Regency, East Java - Cicik Setia Ningsih; Agus Suherman; Hendrik Anggi Setiawan (Universitas Gadjah Mada, 2022)
A successful capture fisheries business requires a fishing port with excellent facilities. This study, therefore, aims to analyze the current facility utilization rate of Pondokdadap, The Coastal Fishing Port (CFP) and formulate a suitable development strategy. The study was conducted using a descriptive survey from January to April 2021. Twenty-four respondents comprising 11 CFP (Coastal Fishing Port) and FAP (Fish Auction Place) employees and 13 fishers and fish traders were obtained using the inclusion criteria. Primary data was collected through structured interviews based on a questionnaire, while secondary data were obtained through literature reviews on books, articles, and journals related to research. Subsequently, an analysis of facility utilization at CFP Pondokdadap was carried out, while a SWOT analysis was performed on the proposed alternative development strategy. Based on the results, the existing physical condition of the facilities is satisfactory, with varying utilization rates. However, the Government and the CFP Pondokdadap management are encouraged to implement other development strategies, for instance, strengthening fisheries competitiveness by maintaining fish quality, optimizing Sempu Island as a natural breakwater and marine aquaculture fisheries, developing a fishery information system, building supporting facilities at CFP Pondokdadap, as well as improving the quality of human resources, apparatus, and fishing communities at CFP Pondokdadap.